Superiority of naked neck over normally feathered white broilers for growth,carcass traits and blood biochemical parameters in tropical climate - Patra, B N; S Bais, R K; Prasad, R B; Singh, B P; Sharma, Deepak; Bhushan, Bharat (The Indian Journal of Animal Sciences, 2005)
A broiler population segregating for the naked neck (Na) gene was used to evaluate its effect on fast growing broilers at heat stress. An experimental stock comparable to those of modem broilers was established by backcrossing to white synthetic male and female lines. Mating between heterozygous (Ndna) males and females produced normally feathered (na/na), heterozygous (Na/na) and homozygous (Na/Na) chicks for the present study. Day-old to 7-week-old white broilers of 3 genotypes, viz. normally feathered (na/na), heterozygous naked neck (Na/na) and homozygous naked neck ( Na/Na ) were compared for heat dissipation, growth performance, body conformation traits, blood biochemical parameters and carcass traits in tropical climate. The naked neck broilers had significantly higher body weight and better feed conversion ratio than na/na broilers. The Na/Na or Na/na broilers exhibited higher giblet yield, blood loss and lower feather mass compared to na/na broilers. The results indicated that the reduction in feather coverage in Na/na and Na/na broilers facilitates better heat dissipation with more body weight gain, better FCR and carcass traits compared to normal broilers.